Larvicidal effectiveness of the ethanolic extract of Annona cherimolia “cherimoya” Miller and A. muricata Linneaus “graviola” seeds against Anopheles sp. - Bobadilla Álvarez, Miguel (2002)
In view of the increase of the resistance produced by chemical pesticides used against mosquitoes as vectors of public health diseases, searching for alternative methods has begun by using plant extracts with larvicidal activity which are environmentally safe and biologically degradable. Under this premise, the aim of the present study was to evaluate the mortality on fourth stage larvae of Anopheles sp. by using ethanolic extract of A. cherimolia (E1) and A. muricata (E2) seeds. The bigger mortality percentages corrected by Abbott’s formula were 100% on the twelveth hour at 8,0 and 12,0 mL/100 mL concentrations in E1 and E2. Morover E2 reached more larval toxic effect than E1 in about 4,58% of mortality. The probit analysis showed an heterogeneous response of the larval individuals towards 50% (LC50) and 90% (LC90) lethal concentrations throughout the evaluation period, and an homogeneity response towards 50% (LT50) and 90% (LT90) lethal times when the concentrations of the extracts were increased. Likewise, the slopes of the log-dosage/probit lines showed larval individuals with different susceptibilities demonstrating the presence of different populations and gene compositions. The work allowed us to evaluate the efficiency of both extracts and to understand the necessity of more assays to ensure the best larvicidal control in such mosquitoes.